Analysis of Teaching Materials for Arabic Textbooks for Islamic Junior High School Based on CEFR Standards - Khambali, Khambali; Asrori, Imam; Rosyidi, Abdul Wahab; Nurhasanah, Nurhasanah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
Today Arabic is no longer the language of the Islamic holy book but has become an international language, the ministry of religion revised the curriculum by adding a special point, namely Arabic learning is directed at communicative. The research method used is content analysis with a qualitative approach. The data collection technique is documentation, while the aim is to determine the suitability of MTs textbooks with CEFR standard measuring instruments. From the results of the analysis it was found that the content of the MTs Arabic textbook material was generally at the level of A1-A2 on the CEFR standard, this level was in accordance with the needs of MTs students, but in terms of presentation it was still not appropriate because the portion of the material was still dominated by understanding the text. it is necessary to readjust the preparation of material that focuses more on the Arabic language needs of students and more contextual and provides a larger portion of language skills practice activities.